VvCCD7, a novel strigolactone synthesis gene in grapevine (Vitis vinifera L.), increases sensitivity to drought and low-phosphorus stress in transgenic Arabidopsis - Wang, Wan-Ni (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.